The Effect of Workshop Facilities on Practice Learning Outcomes of Students of SMKN 1 Tomohon - Mohammad Saleh, Ainun; Mandagi, Gilbert; Kaligis, Gery (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
The purpose of the study was to determine the effect of workshop facilities on students' learning outcomes of electrical power installation engineering practice at SMK Negeri 1 Tomohon. The research method used is a quantitative descriptive method with a simple regression technique. The research population was all Class XI students, Department of Electrical Power Installation Engineering, which amounted to 30 people. The research sample was the entire population, Class XI students of the Department of Electrical Power Installation Engineering, which amounted to 30 people. Workshop facilities are one of the external factors that can improve students' learning outcomes of electrical power installation engineering practice at SMK Negeri 1 Tomohon. The formulation of the research problem is whether there is an influence of workshop facilities on the learning outcomes of students' electrical power installation engineering practice at SMK Negeri 1 Tomohon. The research instrument used to measure workshop facilities was a questionnaire, while for student learning outcomes, it was through a learning evaluation. The study concludes that workshop facilities affect the learning outcomes of electric power installation engineering practices for students of SMK Negeri 1 Tomohon. The study results evidence this obtained a significance value of 0.000 <0.05, and the t-count value is more significant than t-table, namely t-count = 11.191 > t-table 2.048. With the magnitude of the influence of 81.7%.